EFEKTIVITAS KELEMBAGAAN PENGELOLAAN HUTAN TANAMAN RAKYAT DI TINGKAT LOKAL - Fentie Salaka; Iis Alviya; Elvida Y Suryandari; Fitri Nurfatriani; Muhammad Zahrul Muttaqin (Jurnal Analisis Kebijakan Kehutanan, 2020)
Development of Community Plantation Forest (HTR) as one of Social Forestry (SF) Programs in Indonesia seems still not able to optimally improve people's welfare becaused of weak institutional arrangements at local level. The purpose of this study is to analyze the effectiveness of HTR institutional arrangements at local level in encouraging the development of HTR. Data are collected through field observations, in-depth interviews and focus group discussion (FGD and analysed using qualitative descriptive method. The results show that institutional managements of HTR at farm level in four HTR permit holders examined are ineffective and require capacity building program. In addition, institutions in the form of cooperatives are generally better than farmer groups (Kelompok Tani Hutan/KTH); even though, they have not been able to fully implement the rules of the game that have been prepared and agreed by all members. To strengthen local institutional arrangements, after granting permits to communities, it is necessary for governments to intensify facilitation program in the form of guidance and technical training in forest management administration and finance management, development of potential HTR products and options of market opportunity.